Making sense of the big picture: Maps with gender factors to improve project targeting - Pfeifer, Catherine (International Livestock Research Institute, 2016)
Catherine Pfeifer took up the challenge of integrating gender into the maps she produced. Starting with an economics model and major gender concepts, she performed a factor analysis on published data, which resulted in six factors or “gender contexts” in Africa. These maps can be used for assessing whether a particular technology might be adopted in a certain context. Interview with Catherine Pfeifer (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684